Leptin and leptin receptor gene polymorphisms and depression treatment response - Tavast, Ida-Maria; Solismaa, Anssi; Lyytikainen, Leo-Pekka; Mononen, Nina; Moilanen, Eeva; Hamalainen, Mari; Lehtimaki, Terho; Kampman, Olli (Cambridge University Press (CUP), 2025)
Objective:Associations between leptin (LEP) and leptin receptor (LEPR) gene polymorphismsand mood disorders have been found but not yet confirmed in multiple studies. The aim of ourstudy was to study the associations betweenLEPandLEPRsingle nucleotide polymorphisms(SNPs) and treatment response of depression. Associations between leptin levels anddepression severity were also investigated.Methods:The data included 242 depressed patientsin secondary psychiatric care. Symptoms of depression were assessed with the Montgomery-& Aring;sberg Depression Rating Scale (MADRS). Previously foundLEPandLEPRSNPs associatedwith depression and other mood disorders were studied. Furthermore, all availableLEPandLEPRSNPs were clumped using proxy SNPs to represent gene areas inr(2)>0.2 linkagedisequilibrium and their association with treatment response was analysed with logisticregression.Results:Two proxy SNPs ofLEPRgene, rs12564738 and rs12029311, were associatedwith MADRS response at 6 weeks (padjusted=0.024,padjusted=0.024). SNPs from previousstudies were not associated with MADRS response, butLEPRrs12145690 from a previous studywas strongly associated with rs12564738 (r(2)=0.94). The positive association between leptinlevels and MADRS score at baseline after adjusting with age, sex, body mass index (BMI),Alcohol Use Disorders Identification Test score, and smoking was found (p=0.011).Conclusion:Our findings suggest thatLEPRpolymorphisms are associated with depressiontreatment response. We also found associations between leptin levels and depressionindependently of BMI. Further studies and meta-analyses are needed to confirm thesignificance of found SNPs and the role of leptin in depression.